2021
DOI: 10.1016/j.tracli.2021.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent Plasma Therapy in the management of COVID-19 patients-The newer dimensions

Abstract: Background COVID 19 infection caused by novel coronavirus with no specific established treatment. Convalescent Plasma Therapy has been authorized as an off-label therapeutic procedure. We assessed the outcome of convalescent plasma (CP) units versus standard treatment on the complete recovery, improvement and 28 days’ mortality of COVID 19 patients. Materials and methods The present was multi-centric case controlled observational prospective study. The study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…A total of 4728 records were identified from databases, websites and citation searching. There were 47 studies 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 fulfilled the inclusion criteria and were used for the systematic review and meta‐analysis (Figure 1 ). Of 47 included studies, 21 were clinical trials 16 , 17 , 18 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 4728 records were identified from databases, websites and citation searching. There were 47 studies 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 fulfilled the inclusion criteria and were used for the systematic review and meta‐analysis (Figure 1 ). Of 47 included studies, 21 were clinical trials 16 , 17 , 18 ,…”
Section: Resultsmentioning
confidence: 99%
“…Of 47 included studies, 21 were clinical trials 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 60 , 61 , 62 and 26 were observational studies. 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 55 , 56 , 57 , 58 , 59 Among clinical trials, there were 18 studies published in peer‐reviewed journals 16 , 17 , 18 , 19 , 20 , 21 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis conducted by Luo et al ( 43 ) put forward that patients with severe COVID-19 benefit more from the CCP transfusion; so we conducted the subanalysis and we found that there was a significantly lower 28-day mortality rate in the severe and critical patients treated with CP compared with the control groups (41/276 vs. 47/199, P = 0.02, OR 0.58 95% CI 0.36–0.93). An observational prospective study ( n = 2,432) also offers an evidence that CP group has a lower mortality than the nontransfused group in the critical cases (44.3 vs. 48.9%) ( 47 ). Our analysis should be interpreted with caution as only one of the five RCTs showed a reduction in 28-day mortality, but the sample size of this study accounted for 46% of the weight in the meta-analysis, suggesting the results were largely dominated by this trial.…”
Section: Discussionmentioning
confidence: 99%